The Impact Of Cash Flows On Capital Adequacy Ratio: A Comparative Study Of Indonesian And Malaysian Commercial Banks - Samryn, La Madjid (2019)
Cash flow is the movement of cash, which is a medium of the transactions in carrying out the banks’ operating, investing, and financing activities. At managing the cash flow, instead of the Indonesians, Malaysian commercial banks showed an average lower Capital Adequacy Ratio but operationally exhibited better capability in business expansion. This study aims to measure the significance of differences in the impacts of Cash Flows on Capital Adequacy Ratio between the commercial banks in the two countries. For the comparisons, this study uses the secondary data of Cash Flows and Capital Adequacy Ratio from 2009 to 2013 of the big five banks of the countries. Application of Chow statistics on avail data showed that the Cash Flow from Investing Activities of the two countries shows the different impact on Capital Adequacy Ratio. Cash Flow from Investing Activities is the most influencing cash flow on the Capital Adequacy Ratio. Accordingly, these findings reinforce the implication that Malaysian commercial banks are more stable and reliable due to the well-managed investment as a source of cash flow and capitalized income. Hence, this study recommends the Malaysian banking authority to sponsor the establishment of a banking restructuring institution for ASEAN countries. To the Indonesian banking authority, this study recommends the improvement of investing activities and merge the small commercial banks to enforce the banks’ capital strengthening.